Complete Transfer of Perceptual Learning across Retinal Locations Enabled by Double Training - Xiao, Lu-Qi (2008)
Practice improves discrimination of many basic visual features, such as contrast, orientation, positional offset, etc. [1–7]. Perceptual learning of many of these tasks is found to be retinal location specific, in that learning transfers little to an untrained retinal location [1, 6–8]. In most perceptual learning models, this location specificity is interpreted as a pointer to a retinotopic early visual cortical locus of learning [1, 6–11]. Alternatively, an untested hypothesis is that learning could occur in a central site, but it consists of two separate aspects: learning to discriminate a specific stimulus feature (“feature learning”), and learning to deal with stimulus non-specific factors like local noise at the stimulus location (“location learning”) [12]. Therefore, learning is not transferable to a new location that has never been location-trained. To test this hypothesis we developed a novel double-training paradigm that employed conventional feature training (e.g., contrast) at one location, and additional training with an irrelevant feature/task (e.g. orientation) at a second location, either simultaneously or at a different time. Our results showed that this additional location training enabled a complete transfer of feature learning (e.g., contrast) to the second location. This finding challenges location specificity and its inferred cortical retinotopy as central concepts to many perceptual learning models, and suggests perceptual learning involves higher non-retinotopic brain areas that enable location transfer.